Influence of maternal height and weight on low birth weight: a cross-sectional study in poor communities of northeastern Brazil. - Revilane Parente de Alencar Britto; Telma Maria Toledo Florêncio; Ana Amelia Benedito Silva; Ricardo Sesso; Jairo Calado Cavalcante; Ana Lydia Sawaya (PLoS ONE, 2013)
BACKGROUND: Low birth weight (LBW) is associated with an increased risk of mortality, adverse metabolic conditions, and long-term chronic morbidities. The relationship between LWB and short maternal stature coupled with nutritional status was investigated in poor communities. METHODS/PRINCIPAL FINDINGS: A cross-sectional population-based study involving 2226 mother-child pairs was conducted during the period 2009-2010 in shantytowns of Maceió, Alagoas, Brazil. Associations between LBW and maternal sociodemographics, stature and nutritional status were investigated. The outcome variable was birth weight (< 2500 g and ≥ 2500 g). The independent variables were the age, income, educational background, stature and nutritional status (eutrophic, underweight, overweight and obese) of the mother. The frequency of LBW was 10%. Short-statured mothers (1(st) quartile of stature ≤ 152 cm) showed a tendency of increased risk of LBW children compared to mothers in the 4(th) quartile of stature (>160.4 cm) (OR: 1.42, 95% CI: 0.96 - 1.09, p = 0.078). Children from short-statured mothers weighed an average of 125 g less than those from taller mothers (3.18 ± 0.56 kg vs. 3.30 ± 0.58 kg, respectively p = 0.002). Multivariate analyses showed that short stature, age < 20 y (OR: 3.05, 95% CI:1.44 - 6.47) or were underweight (OR: 2.26, 95% CI:0.92 - 5.95) increased the risk of LBW, while overweight (OR: 0.38, 95% CI:0.16 - 0.95) and obesity (OR: 0.39, 95% CI:0.11 - 1.31) had lower risk for LBW. In taller mothers, lower income and underweight were associated with LBW (OR: 1.88, 95% CI: 1.07 - 3.29 and 2.85, 95% CI:1.09 - 7.47, respectively), and obese mothers showed a trend of increased risk of LBW (OR: 1.66, 95% CI:0.84 - 3.25). CONCLUSIONS/SIGNIFICANCE: Overweight was found to have a protective effect in short-statured mothers, indicating that a surplus of energy may diminish the risk of LBW. Short-statured younger mothers, but not taller ones, showed higher risk of LBW. The mother being underweight, regardless of stature, was associated with LBW.